KINDERGARTEN TEACHER’S ABILITY IN TEACHING MATH IN TK PEMBINA OF PEKANBARU CITY - Yeni Solfiah (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2018)
Kindergarten is an educational service for an early childhood. There are many activities that can stimulate children’s ability in kindergarten, there are religious-morals value, social-emotional, physical motor, language, cognitive, and art. For the cognitive value, one of them is mathematical learning. For an early childhood, mathematical learning is done without coercion and not teach in a hurry methods, but it is done in a fun way to attract the children. Teachers as educators must also have the ability that qualified in teaching and in making the learning materials. However, the fact are teachers thought that teaching math for early childhood is difficult, learning looks unattractive and not challenging because the teachers limited the creativity just by introducing the numbers. This research consist some of indicators, there are indicator by the curriculum component it’s consist a content, process, environment / material and center of interest of the child, indicator by the instruction component it’s consist an experience planning, interaction, class management and involving parents, indicator by the assessment component it’s consist to benefiting the children, observing and listening the children, using various of sources, and children's assesment learning and development. Based on the data results, the percentage of overall indicators of teacher's ability in teaching math is 78.1% with "quite conducive" category. The highest percentage was in the indicator of observation and listening the children 81.1% with "conducive" category, while the lowest percentage was in the indicator of parent involvement 71% with "quite conducive" category.